Formation of Indoles, Dihydroisoquinolines, and Dihydroquinolines by Ruthenium-Catalyzed Heterocyclizations - Varela-Fernández, Alejandro; Varela, Jesús A.; Saá, Carlos (Synthesis, 2012)
Indoles, dihydroisoquinolines, and dihydroquinolines were efficiently prepared by ruthenium-catalyzed heterocyclizations of aromatic homo- and bis-homopropargyl amines/amides in the presence of an amine/ammonium base-acid pair. These regioselective 5-endo and 6-endo cyclizations most probably occur by nucleophilic trapping of key ruthenium-vinylidene intermediates.
Keywords: heterocyclizations; indoles; isoquinolines; quinolones; ruthenium; vinylidenes